Treatment Patterns and Antipsychotic Medication Adherence Among Commercially Insured Patients With Schizoaffective Disorder in the United States. Issue 5 (October 2016) - Joshi, Kruti; Lin, Jay; Lingohr-Smith, Melissa; Fu, Dong-Jing; Muser, Erik
Abstract : Abstract: This study assessed real-world treatment patterns and antipsychotic (AP) medication adherence among commercially insured US patients with schizoaffective disorder (SCA). Continuously insured adults aged 18 years or older with a diagnosis of SCA from January 1, 2009, to December 31, 2012, were identified from the Clinformatics Data Mart database. Patients were categorized into 2 cohorts: incident or prevalent SCA. Demographics and clinical characteristics were evaluated during the baseline period. Use of psychiatric medications and adherence to AP medications were evaluated during a 12-month follow-up period after index diagnosis of SCA. Of the overall study population (N = 2713; mean age, 40.2 y; 52.7% female), 1961 patients (72.3%) (mean age, 38.7 y; 51.3% female) had incident SCA, and 752 patients (27.7%) (mean age, 43.9 y; 56.5% female) had prevalent SCA. Antipsychotics were used by 74.8% of patients in the overall study population during the follow-up period. The most commonly prescribed oral AP was risperidone (23.9%), followed by quetiapine (21.4%) and aripiprazole (20.4%). Use of any long-acting injectable APs in the overall study population during the follow-up period was less than 3%. A total of 49.0% and 38.0% of the overall study population had medication possession ratios and proportion of days covered for APs of 80% or greater, respectively. Overall use of long-acting injectable APs for the treatment of SCA is low, and adherence to AP medications, measured by both medication possession ratio and proportion of days covered, is suboptimal among patients with SCA in the real-world setting.